2016
DOI: 10.1093/jac/dkw279
|View full text |Cite
|
Sign up to set email alerts
|

WGS analysis and molecular resistance mechanisms of azithromycin-resistant (MIC >2 mg/L)Neisseria gonorrhoeaeisolates in Europe from 2009 to 2014

Abstract: Clonal spread of relatively few N. gonorrhoeae strains accounts for the majority of the azithromycin resistance (MIC >2 mg/L) in Europe. The four isolates with high-level resistance to azithromycin (MIC ≥256 mg/L) were widely separated in the phylogenomic tree and did not belong to any of the main clades. The main azithromycin resistance mechanisms were the A2059G mutation (high-level resistance) and the C2611T mutation (low- and moderate-level resistance) in the 23S rRNA gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 37 publications
4
66
0
1
Order By: Relevance
“…Chromosomal mutations mediating low‐level resistance to beta‐lactams and tetracycline are common in N. gonorrhoeae isolates, and they are widespread across the phylogeny . While azithromycin resistance is less common than resistance to previously used drugs, resistance or reduced susceptibility has arisen across a large number of genomic backgrounds . In contrast, reduced susceptibility to ESCs (ESC‐RS) is primarily clonal, and the majority of ESC‐RS isolates belong to only a few major lineages .…”
Section: From Pathogen To Superbug: Treatment and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Chromosomal mutations mediating low‐level resistance to beta‐lactams and tetracycline are common in N. gonorrhoeae isolates, and they are widespread across the phylogeny . While azithromycin resistance is less common than resistance to previously used drugs, resistance or reduced susceptibility has arisen across a large number of genomic backgrounds . In contrast, reduced susceptibility to ESCs (ESC‐RS) is primarily clonal, and the majority of ESC‐RS isolates belong to only a few major lineages .…”
Section: From Pathogen To Superbug: Treatment and Resistancementioning
confidence: 99%
“…22 While azithromycin resistance is less common than resistance to previously used drugs, resistance or reduced susceptibility has arisen across a large number of genomic backgrounds. 22,78,79 In contrast, reduced susceptibility to ESCs (ESC-RS) is primarily clonal, and the majority of ESC-RS isolates belong to only a few major lineages. 22,50 In isolates from the United States, azithromycin reduced susceptibility (AZI-RS) is estimated to have been acquired 75 times, and reversion to susceptibility is also relatively frequent (42 times).…”
Section: Acquisition Of Antibiotic Resistancementioning
confidence: 99%
“…Effective STI control will require the political will to prioritise and invest in new 150 rapid molecular methods for predicting AMR (for AMR surveillance but ideally also to inform individualized treatment), [190][191][192] rapid point of care tests for diagnosis of gonorrhoea (ideally with combined prediction of AMR); 190,191 ideal phylogenomics of gonococci and their AMR (also in non-cultured samples); 159,457,[459][460][461][462][463][464] and appropriate models for pharmacokinetics/ pharmacodynamics (urogenital and extragenital sites) and prediction of AMR induction/selection, evolution and biological fitness. -Data are for principal diagnosis, recorded using the ICD-9-CM from 1993-94 to 1997-98, and recording using the ICD-10-AM (Australian modification) from 1998-99.…”
mentioning
confidence: 99%
“…DNA sequence analysis revealed that all 14 isolates harbored the mosaic-mtr and the A2059G mutation in all four copies of their 23S rRNA gene. While investigators from many countries have reported on the A2059G mutation or the mosaic-mtr, none described these two haplotypes together (5,10,(12)(13)(14)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). The 14 isolates in this study are the first known isolates to have possessed both the A2059G mutation and the mosaic-mtr.…”
Section: Resultsmentioning
confidence: 79%